Quantitative study of the effects of early standardized ambulation on sleep quality in patients after hepatectomy - Chun-yan Ni; Chun-yan Ni; Guo-jun Hou; Ya-yuan Tang; Jing-jing Wang; Wen-jun Chen; Yuan Yang; Zhi-hong Wang; Wei-ping Zhou (Frontiers in Surgery, 2022)
BackgroundSleep quality has been always an important problem for patients after hepatectomy. The main purpose of the study is to investigate the effects of early ambulation on sleep quality in patients after liver resection via a quantitative study.MethodsPatients undergoing liver tumor resection were randomly divided into two groups, and the Pittsburgh Sleep Quality Index (PSQI) was used to assess the postoperative activities and sleep quality.ResultsPatients who started early ambulation after liver resection had significantly better sleep quality, faster recovery of gastrointestinal function and shorter lengths of postoperative hospital stay compared with the control group. And there was no significant difference in the incidence of postoperative complications between the two groups.ConclusionEarly standardized physical activities are feasible for patients after liver resection, which can significantly improve patient's sleep quality, reduce patient's pain and the nursing workload, and achieve rapid recovery.